KARAKTERISTIK MESIN PENDINGIN ENERGI SURYA DENGAN PASANGAN METANOL DAN KARBON AKTIF (Characteristics of Solar Refrigerator with Methanol and Activated Carbon Pair) - Sitorus, Tulus B; Napitupulu, Farel H.; Ambarita, Himsar (Baristand Industri Banda Aceh, 2013)
While the current energy crisis, renewable energy such as solar energy isone solution. One application of the utilization of solar energy is adsorption refrigeratorsystem. Besides interestingly enough, research on adsorption refrigerator cycle solarenergy is still rare in Indonesia. This study aimed to obtain the characteristics of anadsorption refrigerator cycle using solar energy. The measurement of solar radiationusing a pyranometer. Testing of solar adsorption refrigerator using activated carbonadsorbent as much as 8 kg, 2 litres of methanol refrigerant and water as a cooling medium2.5 litres. The area of collector is 0.25 m2. From the test results obtained maximum valueof COP 0.064 on April 3, 2012 and a minimum value of COP 0.028 obtained on April 4,2012. The maximum value of the specific cooling power obtained 8.4578 kW / kg on April2, 2012 and a minimum value of SCP obtained on April 3, 2012 of 8.3564 kW/kg. Thelowest water temperature that can be achieved during the process of adsorption on April 6,2012 is 8.24oC. The average of water temperature during the adsorption process for theseven days of testing ranged from 8.24Â°C - 11.17 oC.